Understanding resistance in lean implementation in healthcare environments: an institutional logics perspective. Issue 4 (12th March 2022) - Akmal, Adeel; Foote, Jeff; Podgorodnichenko, Nataliya; Greatbanks, Richard; Gauld, Robin
Abstract: While lean thinking has been used in healthcare for almost two decades, its efficacy has been debated extensively by researchers and practitioners alike. This ongoing debate is largely due to the varied results of its implementation; and resistance to change is considered to be the primary reason behind this variation. This study adopts an institutional logics perspective to analyze the nature of this resistance by drawing attention to how clinical staff make judgements about the appropriateness, acceptability and legitimacy of lean thinking. To conceptualize resistance, a systematic literature review based on 33 published studies depicting lean implementations was conducted, which helped to develop a nuanced understanding of resistance and its causes. Subsequently, 47 semi-structured interviews were undertaken with Quality Improvement managers regarding their experience with implementing lean thinking in 15 New Zealand District Health Boards. These interviews were used to identify and evaluate strategies used to minimize resistance within the implementation of lean initiatives in healthcare organizations. The findings of this research suggest that typically there are three strategies adopted by quality improvement managers—(1) communication strategies to create a better narrative for lean implementation; (2) cooperation strategies, which encourage the adherents of lean and medical logics to work together on shared problems, creating opportunities for them to learn about other logics; and (3) performance management strategies with the help of incentives and commitment devices to create a supportive environment for lean implementation. Together, these strategies work to improve the availability, accessibility, and activation of lean thinking logic in healthcare.